A Biomimetic Nanomedicine Targets Orthotopic Glioblastoma by Combinatorial Co‐Delivery of Temozolomide and a Methylguanine‐DNA Methyltransferase Inhibitor. Issue 12 (20th September 2022) - Wang, Yibin; Sun, Yajing; Geng, Nan; Zheng, Meng; Zou, Yan; Shi, Bingyang
Abstract: Glioblastoma (GBM) is the most aggressive intracranial tumor that occurs in the central nervous system (CNS) and has no effective treatment due to the fact of drug resistance. To combat drug resistance, TMZ is generally administrated in combination with other chemotherapeutic drugs. Unfortunately, drug combinations used to date only show modest improvements in anti‐tumor effects and have increased toxicity. Herein, an ApoE peptide decorated GBM cancer cell membrane camouflaged nanomedicine (AMNPs@TMZ+LM) to specifically co‐deliver TMZ and the MGMT inhibitor lomeguatrib (LM) for combinatorial GBM treatment is developed. Incorporation of LM not only effectively suppresses the repair of damaged DNA, but also inhibits tumor cell proliferation by inducing cell cycle arrest. Importantly, this biomimetic nanomedicine achieves high BBB penetration and enhances sensitivity to both TMZ‐resistant (U251‐TR) and GBM stem cells (GSCs). Notably, AMNPs@TMZ+LM results in significant inhibition of the growth of orthotopically implanted U251‐TR tumor in mice. In comparison, treatment with single drug loaded nanomedicines results in compromised anti‐GBM effects. Histological analyses and blood parameter studies show good biocompatibility of the nanomedicine. Hence, this biomimetic nanomedicine provides a potential new approach to overcome the limitations of current GBM chemotherapy regimens by co‐delivery of TMZ and the MGMT inhibitor LM. Abstract : This work develops an ApoE peptide decorated GBM cell membrane camouflaged nanomedicine to co‐deliver TMZ and the MGMT inhibitor lomeguatrib (LM) for combinatorial GBM treatment. Co‐delivery of LM not only effectively suppresses the repair of damaged DNA, but also acts by inhibiting cell proliferation, resulting in enhanced sensitivity to both U251‐TR and GBM stem cells.